2008
DOI: 10.1002/ajmg.a.32204
|View full text |Cite
|
Sign up to set email alerts
|

Tetralogy of Fallot associated with pulmonary atresia and major aortopulmonary collateral arteries in a patient with interstitial deletion of 16q21–q22.1

Abstract: A newborn male had an interstitial deletion of 16q21-q22.1 accompanying tetralogy of Fallot associated with pulmonary atresia and major aortopulmonary collateral arteries (MAPCA), dysmorphic craniofacial features, failure to thrive, and severe psychomotor developmental delay. When the deletion in this patient and other reported patients are compared, the 16q22 region appears to be the smallest region for 16q deletion syndrome. Since over 50% of patients with the deletion of 16q22 region have congenital heart d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
(49 reference statements)
0
16
0
Order By: Relevance
“…The accurate molecular characterisation performed here might contribute to better define candidate regions for specific phenotypic signs, such as CHD. Yamamoto et al [1] compared their proband presenting CHD to a group of 13 previously described patients, with overlapping deletion encompassing the 16q21q22 tract. Nine patients out of 14 (64%) showed CHD, mainly related to endocardial cushion and outflow-tract defects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The accurate molecular characterisation performed here might contribute to better define candidate regions for specific phenotypic signs, such as CHD. Yamamoto et al [1] compared their proband presenting CHD to a group of 13 previously described patients, with overlapping deletion encompassing the 16q21q22 tract. Nine patients out of 14 (64%) showed CHD, mainly related to endocardial cushion and outflow-tract defects.…”
Section: Discussionmentioning
confidence: 99%
“…Nine patients out of 14 (64%) showed CHD, mainly related to endocardial cushion and outflow-tract defects. By analysing the overlapping regions, the authors hypothesised that a candidate region for CHD could be identified between the middle part of 16q21 and the middle of 16q22 (from 62,000,000 to 68,000,000) [1]. The 16q21 band, with a very low gene density, is not the major candidate, as it represents a wide region of euchromatic copy number variations (CNV) without phenotypic effect [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are only a few reports in medical literature with regard to patients with larger, cytogenetically visible deletions comprising this region, mostly because of an unbalanced complex chromosomal rearrangement. [19][20][21][22][23][24][25][26][27][28][29] In this study, we aimed to characterize the clinical and molecular features of four patients with submicroscopic interstitial 16q24.3 microdeletions ascertained by genome-wide array analysis and to determine the shortest region of overlap (SRO) to identify candidate genes responsible for their overlapping phenotype.…”
Section: Introductionmentioning
confidence: 99%